Reaction to Michael Oriard’s “NCAA Academic Reform: History, Context and Challenges” - Smith, Ronald A. (Journal of Intercollegiate Sport, 2012)
The purpose of this paper is to provide a response to Michael Oriard’s keynote address. Similar to Oriard’s analysis, the author adopts a historical approach to examine academic reform and its drivers within the intercollegiate athletics context. The author suggests that faculties, students, and boards of trustees should play key roles in academic reforms, and also proposes several reform options.